Econeurobiology and brain development in children: key factors affecting development, behavioral outcomes, and school interventions - Mualem, Raed; Morales-Quezada, Leon; Farraj, Rania Hussein; Shance, Shir; Bernshtein, Dana Hodaya; Cohen, Sapir; Mualem, Loay; Salem, Niven; Yehuda, Rivka Riki; Zbedat, Yusra; Waksman, Igor; Biswas, Seema (Frontiers in Public Health, 2024)
The Econeurobiology of the brain describes the environment in which an individual's brain develops. This paper explores the complex neural mechanisms that support and evaluate enrichment at various stages of development, providing an overview of how they contribute to plasticity and enhancement of both achievement and health. It explores the deep benefits of enrichment and contrasts them with the negative effects of trauma and stress on brain development. In addition, the paper strongly emphasizes the integration of Gardner's intelligence types into the school curriculum environment. It emphasizes the importance of linking various intelligence traits to educational strategies to ensure a holistic approach to cognitive development.In the field of Econeurobiology, this work explains the central role of the environment in shaping the development of the brain. It examines brain connections and plasticity and reveals the impact of certain environmental factors on brain development in early and mid-childhood. In particular, the six key factors highlighted are an environment of support, nutrition, physical activity, music, sleep, andcognitive strategies, highlighting their potential to improve cognitive abilities, memory, learning, self-regulation, and social and emotional development. This paper also investigates the social determinants of health and education in the context of Econeurobiology. It emphasizes the transformative power of education in society, especially in vulnerable communities facing global challenges in accessing quality education.